Analyzing the Epic of Mem and Zin According to Vladimir Propp’s Narratology - Saleh , Chaware; Ahmed , Saya (Humanities Journal of University of Zakho, 2023)
This study is an attempt to analyze the plot of Ehmedê Xanî(1650-1707)’s Mem and Zin based on Vladimir Propp’s (1895-1970) Narrative Theory who is a Soviet folklorist. The effort is to find out how many functions have appeared in the epic and to point out seven broad character types that are mentioned by Propp in his most famous book the Morphology of the Folktale (1928). There are several theories that analyze some basic elements of stories, such as Joseph John Campbell’s “The Hero’s Journey” and Maureen Murdock’s “The Heroine’s Journey”. But among all, this paper has chosen a narratology structuralism study which has been explained by Propp. His theory is one of the well-spread theories and views all literature genres in the form of certain fixed structures.